Pete Sparaco and John Dowden, circa 1960-1969 (1960)
Pete Sparaco, member of the Newman Club and the Men's Glee Club in 1961, alongside John Dowden, an Architectural Engineering student who lived on the third floor of Tenaya Hall in 1963. Both are absorbed in their study of delineation during a morning class.